Pelatihan Pengolahan dan Pemasaran Keripik Pisang sebagai Upaya Meningkatkan Perekonomian Masyarakat Desa Curah Kalong - Masrurotullaily Masrurotullaily; Muhammad Sohib; Hikmal Nanta Kusuma W.A.; Muhammad Rabbani Rasyid; Farida Dewiyanti; Sri Wahyuni Handayani; Nur Insaniyah; Ihsan Robithuz Zaman; Umroh Nurul Faradisa; Nurul Hidayaturrohmah; Laily Ainun Nafis; Muhammad Fijhai Maulana (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Curah Kalong Village is one of the villages with abundant banana availability throughout the year. However, this potential has not been optimized to improve the community's economy in a sustainable manner. Therefore, a community service program was designed to develop processed bananas into value-added products, namely banana chips. The approach used in this program is Asset-Based Community Development (ABCD), which is a community empowerment model based on local strengths. The results of the community service program show that through the ABCD approach, the local potential of the community can be developed, such as increasing the knowledge and skills of the community in processing bananas into quality chips, creating social media accounts for marketing so that banana chips products are better known in a wider environment, forming small business groups that are ready to develop production independently, and increasing the community's motivation to become entrepreneurs as well as household income opportunities. This ABCD-based program also fosters self-confidence and collective commitment to make banana chips a sustainable flagship product of the village.